2015
DOI: 10.1177/1077558715596470
|View full text |Cite
|
Sign up to set email alerts
|

Associations Between Family Ratings on Experience With Care and Clinical Quality-of-Care Measures for Nursing Home Residents

Abstract: Several states are currently collecting and publicly reporting nursing home resident and/or family member ratings of experience with care in an attempt to improve person-centered care in nursing homes. Using the 2008 Maryland nursing home family survey reports and other data, this study performed both facility- and resident-level analyses, and estimated the relationships between family ratings of care and several long-term care quality measures (pressure ulcers, overall and potentially-avoidable hospitalizatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
24
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 33 publications
1
24
0
Order By: Relevance
“…Study results are consistent with prior literature examining associations between ownership change and reduced NH quality (Banaszak-Holl et al, 2002; Cadigan, Stevenson, Caudry, & Grabowski, 2014; Harrington et al, 2012; Stevenson & Grabowski, 2008) and add to the nascent body of literature on consumer-reported experience with care in the NH setting (Frentzel et al, 2012; Li et al, 2013; Li, Li, & Tang, 2014). The NH quality metrics examined in prior studies of ownership changes, such as nurse staffing and clinical outcomes (e.g., pressure ulcer rate), may not allow for comprehensive assessment of resident welfare and person-centered care.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Study results are consistent with prior literature examining associations between ownership change and reduced NH quality (Banaszak-Holl et al, 2002; Cadigan, Stevenson, Caudry, & Grabowski, 2014; Harrington et al, 2012; Stevenson & Grabowski, 2008) and add to the nascent body of literature on consumer-reported experience with care in the NH setting (Frentzel et al, 2012; Li et al, 2013; Li, Li, & Tang, 2014). The NH quality metrics examined in prior studies of ownership changes, such as nurse staffing and clinical outcomes (e.g., pressure ulcer rate), may not allow for comprehensive assessment of resident welfare and person-centered care.…”
Section: Discussionsupporting
confidence: 87%
“…Clinically-oriented measures are important in determining the technical aspects of care quality, but residents and family members may view less clinical factors, such as physical environment, communication with care staff, and engagement with care, as better indicators of NH experience. Experience with care ratings can measure these factors, which are likely not accounted for in existing clinical measures (Li, Li, et al, 2014), and may give prospective consumers a more practical understanding of resident experience.…”
Section: Discussionmentioning
confidence: 99%
“…Studies commonly included all residents (n=12) 19 22–25 27 29–32 36 37 or all residents aged 65 years and older (n=7). 8 18 26 33 34 38 39 One study included residents aged 50 years and older 28 and one study included all residents under the age of 106 years. 35 A total of four studies focused on residents newly admitted to the facility 19 30 32 35 and three studies on long-stay residents, 18 33 38 while most studies (n=13) included all types of NHRs.…”
Section: Resultsmentioning
confidence: 99%
“…A recent study on Maryland nursing home found that higher family ratings are associated with risk-adjusted quality measures, 30 including but not limited to nursing staffing and deficiency citations. Therefore, it is possible that residents reporting low satisfaction ratings in facilities of medium and large for-profit chains receive worse quality of care and have worse outcomes.…”
Section: Discussionmentioning
confidence: 99%